Mekanisme Kultural sebagai Counter-Radikalisme: Mengurai Narasi Terorisme Muslim Sasak di Nusa Tenggara Barat (NTB) - Noorhayati, Siti Mahmudah (JURNAL AT-TURAS, 2020)
The idea of intensification of cultural mechanisme is based on an innitiative to strenghten narration of local islam as mediation between moderate, radical, and militant groups in West Nusa Tenggara (NTB) in which most of the inhabitants are Sasak Muslim. This article attempts to trace the possible implementation of cultural mechanisme as a responsive effort to the narration of radicalism among moderate people in NTB. This study also analyze a construction of terrorism and radicalism narration, types of their acceptances and diffusions in ntb, then build a formulated recommendations for dealing with these issues. Keywords: Cultural Mechanism, Counter-Radicalism, Narration of Terrorism, West Nusa Tenggara